Operational parameter optimisation of MZI-SOA using multi-objective genetic algorithms - Dionísio, R. P. (2023)
A methodology for achieving the best-fit set of parameters for a Mach-Zehnder interferometer with a semiconductor optical amplifier (MZI-SOA) static model is proposed. A multi-objective genetic algorithm is exploited and the quality of the approach is validated by applying it in an existing sample. Optimisation of performance and determination of operational limits are enabled by the proposed methodology and good agreement was obtained between simulated and practical results. © 2011 The Institution of Engineering and Technology.